Intimate Partner Violence and Subsequent Violent Offending Among Handgun Purchasers - Tomsich, Elizabeth (Journal of interpersonal violence, 2022)
Perpetrators of intimate partner violence (IPV) often reoffend, and firearm access increases risk of severe injury or fatality. Prior research identifies an association between a history of violent misdemeanor convictions among handgun purchasers and increased risk of subsequent arrest for a violent crime; the risk associated specifically with an IPV criminal history remains largely unexplored. The current study examined a cohort of 76,311 California adults who legally purchased a handgun in 2001 and followed them through 2013. Compared with purchasers who had no criminal history at the time of purchase, those with a history of only IPV (n = 178) charges were at increased risk of subsequent arrest for a violent Crime Index crime (murder, rape, robbery, aggravated assault; adjusted hazard ratio [AHR], 2.6; 95% confidence interval [CI]: 1.4?5.1), any violent crime (AHR, 3.2; 95% CI: 2.0?5.1), and an IPV crime (AHR, 5.2; 95% CI: 3.0?9.0). Purchasers with both IPV and non-IPV charges demonstrated the greatest risk of re-arrest relative to those with no criminal history. Despite the strength of the relationship between IPV and subsequent arrest, a small proportion of handgun purchasers with an IPV criminal history were re-arrested for firearm violence crimes, limiting application for risk assessment purposes. Results affirm prior research identifying IPV as a risk factor for future offending.